I got help for this problem before, but just checked and it's not correct.
What am I doing wrong with this problem?
f(x)=3sqrt(5-x)+3
y=3sqrt(5-x)+3
3sqrt(5-x)=y-3
(3sqrt(5-x)^3=(y-3)^3
5-x=(y-3)^3
x=-(y-3)^3-5

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

last step

This is the help I got, but it's still not correct.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.